2015
DOI: 10.1038/srep17091
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of colistin for the treatment of Acinetobacter baumannii infection

Abstract: Multidrug resistant among Acinetobacter baumannii infection is associated with a high mortality rate and limits the therapeutic options. The aim of this study was to assess the safety and efficacy of colistin monotherapy vs. other single antibiotic therapy AND colistin-based combination therapy (with other antibiotics) vs. colistin alone for the treatment of Acinetobacter baumannii infection. Online electronic database were searched for studies evaluating colistin with or without other antibiotics in treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 42 publications
(42 reference statements)
5
29
1
6
Order By: Relevance
“…The excess mortality in the tigecycline group is attributed to patients with tigecycline minimum inhibitory concentration (MIC) >2 mg/L. The meta-analysis by Chen et al on infections by A. baumannii found that colistin-based therapy had better microbiological response than non-colistin therapy but no difference in mortality [25]. In addition, colistin combination therapy, compared with colistin monotherapy, had higher clinical response but no difference in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The excess mortality in the tigecycline group is attributed to patients with tigecycline minimum inhibitory concentration (MIC) >2 mg/L. The meta-analysis by Chen et al on infections by A. baumannii found that colistin-based therapy had better microbiological response than non-colistin therapy but no difference in mortality [25]. In addition, colistin combination therapy, compared with colistin monotherapy, had higher clinical response but no difference in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a small prospective trial of 94 patients with carbapenem-resistant A. baumannii , subjects were randomised to receive colistin alone or colistin + fosfomycin and a statistical difference in the infection-related 28-day mortality was not observed (23.1% vs. 16.3%; P = 0.507); however, microbiological cure in the first 72 h (65.7% vs. 78.8%; P = 0.028) and at the end of treatment (84.5% vs. 100%; P = 0.023) did favour combination therapy [56]. A meta-analysis that evaluated the clinical response of patients with MDR A. baumannii treated with colistin alone or in combination found that colistin combinations did not improve clinical response (OR = 1.37, 95% CI 0.86–2.19; P = 0.18), but microbiological response did improve with combination therapy (OR = 2.14, 95% CI 1.48–3.07; P < 0.0001) [57]. Another meta-analysis evaluated all-cause mortality in patients treated with colistin or colistin combinations for carbapenem-resistant Gram-negative bacteria and found no mortality benefit for colistin paired with rifampicin ( P = 0.81), carbapenems ( P = 0.91), tigecycline ( P = 0.77), sulbactam ( P = 0.81) or aminoglycosides ( P = 0.07) [58].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Various combinations of these drugs have been used for the treatment of CRAB infections; yet, combination therapies were not found to be superior over monotherapies in preventing resistance and improving clinical outcomes, even though the combination therapies may be better at microbiologic eradication (29)(30)(31)(32).…”
mentioning
confidence: 99%